2016
DOI: 10.1016/j.jalz.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal brain structural changes in preclinical Alzheimer's disease

Abstract: Our longitudinal data confirm a biphasic trajectory of changes in brain structure in preclinical AD. These have implications in AD trials, both in patient selection and the use of MRI as a surrogate marker of efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
59
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 49 publications
20
59
1
Order By: Relevance
“…Possibly, our present associations between betweenness centrality and language decline might be part of normal aging, or can be due to pathological processes unrelated to AD. In recent studies in cognitively normal individuals, we have demonstrated associations between amyloid abnormalities and path length in fronto‐temporo‐parietal regions (Tijms et al, ), and thinner temporal cortex to be related to memory decline and disease progression (Pegueroles et al, ; Verfaillie et al, ). We now show that lower path length values in fronto‐temporo‐occipital cortices and precuneus were associated with global cognitive decline.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Possibly, our present associations between betweenness centrality and language decline might be part of normal aging, or can be due to pathological processes unrelated to AD. In recent studies in cognitively normal individuals, we have demonstrated associations between amyloid abnormalities and path length in fronto‐temporo‐parietal regions (Tijms et al, ), and thinner temporal cortex to be related to memory decline and disease progression (Pegueroles et al, ; Verfaillie et al, ). We now show that lower path length values in fronto‐temporo‐occipital cortices and precuneus were associated with global cognitive decline.…”
Section: Discussionmentioning
confidence: 91%
“…Possibly, structural magnetic resonance imaging (MRI) might help identifying those at risk of decline (Dickerson et al, ; Tijms et al, ; Verfaillie et al, ). Evidence is accumulating that brain changes leading to cognitive decline and dementia are not restricted to specific regions such as the medial temporal lobe, but rather include widespread changes in structure, function and organization of the brain (Benzinger et al, ; Dickerson et al, ; Pegueroles et al, ). Patterns of grey matter morphology can be described as a network consisting of multiple small regions of grey matter (i.e., nodes) that are connected to each other when they show structural similarity within a cortex across subjects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studying the influence of new biomarkers is more challenging as the trajectories have been poorly described and they might interact with those already reported, possibly giving nontrivial relationships. In this sense, how the different CSF biomarkers might explain or contribute to each disease atrophy pattern is still uncertain (Idland et al, ; Pegueroles, ).…”
Section: Introductionmentioning
confidence: 99%
“…Only CSF markers significantly correlating with gray matter (GM) volume or brain amyloid load at a significance threshold of voxel-level uncorrected p < 0.001 combined with cluster-level family wise error (FWE)-corrected threshold p < 0.05 are listed in this table. AD (Whitwell et al 2007;Pegueroles et al 2017;Gordon et al 2018). Gray matter volume of the precuneus seems to be a robust early biomarker as it has been shown to predict subsequent whole-brain gray matter volume loss in cognitively healthy individuals over a 6-year follow-up period (Taki et al 2011).…”
Section: Csf Biomarkers Of Pathophysiological Pathways In Admentioning
confidence: 99%